2022
DOI: 10.7150/ijbs.66369
|View full text |Cite
|
Sign up to set email alerts
|

Immune response and potential therapeutic strategies for the SARS-CoV-2 associated with the COVID-19 pandemic

Abstract: Following onset of the first recorded case of Coronavirus disease 2019 (COVID-19) in December 2019, more than 269 million cases and over 5.3 million deaths have been confirmed worldwide. COVID-19 is a highly infectious pneumonia, caused by a novel virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Currently, it poses a severe threat to human health across the globe, a trend that is likely to persist in the foreseeable future. This paper reviews SARS-CoV-2 immunity, the latest developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 181 publications
(146 reference statements)
0
7
0
Order By: Relevance
“…It was known that the early step of SARS-CoV-2 infection includes Spike protruding from the virus envelope, providing specificity to interact with host cell receptors (such as ACE2) and host factors (as TMPRSS2). Inhibition of ACE2 or TMPRSS2 receptors can be potential targets for SARS-CoV-2 prevention [43,44]. In this research, we initially obtained three natural plant extracts, grape stem (Vitis vinifera), gardenia leaf (Gardenia jasminoides), and coffee leaf (Coffea Arabica), that can hinder the interaction of Spike-ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…It was known that the early step of SARS-CoV-2 infection includes Spike protruding from the virus envelope, providing specificity to interact with host cell receptors (such as ACE2) and host factors (as TMPRSS2). Inhibition of ACE2 or TMPRSS2 receptors can be potential targets for SARS-CoV-2 prevention [43,44]. In this research, we initially obtained three natural plant extracts, grape stem (Vitis vinifera), gardenia leaf (Gardenia jasminoides), and coffee leaf (Coffea Arabica), that can hinder the interaction of Spike-ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, the absolute count of CD16+CD56+ NK cells was found in the present study to be statistically lower in the peripheral blood of infected patients compared to both HS (p<0.05) and VS (p<0.001) (Figure 2A) whereas the percentage of CD16+CD56+ NK cells was statistically higher in the infected patients compared to both the HS (p<0.001) and VS (p<0.001) (Figure 2B). In a recent study, CD3-CD56+ natural killer cells were found to be significantly lower in the severe group compared to the healthy subjects whereas the asymptomatic group had higher levels (7,18,20,23). In addition, Zingaropoli et al (11) demonstrated that lower percentage of peripheral blood NK cell was found in COVID-19 patients compared to HS, although not statistically significant.…”
Section: Correlation Studiesmentioning
confidence: 92%
“…Since 2020, the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that cause Coronavirus disease 2019 (COVID-19) has spread globally and created pandemic. SARS-CoV-2 is a positive-sense ssRNA virus and enters host cells by the surface S protein comprising S1 and S2 ( 35 ). The receptor for SARS-CoV-2 is angiotensin-converting enzyme 2 (ACE2) ( Table 1 ).…”
Section: Role Of Viral Infection In the Development Of Asthma Exacerb...mentioning
confidence: 99%
“…SARS-CoV-2 replicates in airway epithelial cells, and TLR3 and TLR7/8 in the endosome and MDA-5 or RIG-1 in the cytosol play roles in the recognition of viral components in a similar way. Severe cases of COVID-19 are assumed to be due to the defect or delay of IFN responses which unlease excessive expression of proinflammatory cytokines/chemokines, called cytokine storm syndrome ( 35 ). Furthermore, other mechanism such as increase in ACE2 signaling, observed in the case of SARS-CoV ( 36 ), may contribute to the immune response to SARS-CoV-2.…”
Section: Role Of Viral Infection In the Development Of Asthma Exacerb...mentioning
confidence: 99%
See 1 more Smart Citation